Survey of Adhesive Systems Knowledge Among Conservative Dentistry Specialist Dentist in Indonesia - Kusumasari, Citra; Aprillia, Iffi; Wijayanti, Wiku Melisa; Abdou, Ahmed (Journal of Indonesian Dental Association, 2023)
Introduction: Knowledge of adhesive systems is an essential item in creating a successful tooth restoration. Adhesive systems are common among dentists in Indonesia, but no research has been found that evaluates the knowledge of the members of Indonesian Conservative Dentistry Association (IKORGI) - Central Jakarta Branch. Objectives: to determine dentists’ understanding regarding the use of adhesive systems during restorative procedures. Methods: This research used a descriptive study with a cross-sectional questionnaire design. One hundred and five dentist specialists in IKORGI - Central Jakarta Branch, completed an online survey form within two months comprising three sections: (a) demographics (6 items), (b) knowledge about the latest technology of adhesive systems (5 items), and (c) clinical implications of adhesive systems (10 items). Data was collected and analyzed using Microsoft excel and IBM SPSS. Results: The primary data was dominated by the female with the range of 0 to 5 years of experience since graduated from conservative dentistry program. They understood the adhesive system quite well, as seen from the maximum score of the respondents was 4.25. Among participants, 63.8% to 99% showed a strong knowledge about the adhesion terminology and type of adhesives. Conclusions: The understanding of adhesive systems knowledge among dentist specialists in IKORGI - Central Jakarta Branch is good, although there are some significant differences between the research variables. Further research is required to cover all areas of Indonesia with or without specialty in conservative dentistry.